Testing, numerical modelling and design of stainless steel welded I-sections under minor-axis combined loading. (15th September 2021) - Sun, Yao; Su, Andi; Jiang, Ke; Liang, Yating; Zhao, Ou
Highlights: The cross-section behaviour of stainless steel welded I-sections under combined loading has been studied. Minor-axis eccentric compression tests on ten stainless steel welded I-section stub columns were conducted. FE models were developed and validated against the test results, and then used to perform parametric studies. The codified design interaction curves were assessed, based on the test and FE data, indicating inaccuracy. New improved design interaction curves were proposed, with the accuracy and reliability demonstrated. Abstract: This paper reports a comprehensive experimental and numerical investigation into the cross-section behaviour and resistances of stainless steel welded I-sections under combined compression and minor-axis bending moment. A testing programme was firstly conducted, including initial local geometric imperfection measurements and minor-axis eccentric compression tests on ten stainless steel welded I-section stub column specimens. Following the testing programme, a numerical modelling programme was performed, where finite element models were developed to simulate the test observations and then used to conduct parametric studies to generate further numerical data over a wide range of cross-section dimensions and loading combinations. Based on the obtained test and numerical data, the accuracy of the design interaction curves, as given in the current European code and American design guide, for stainless steel welded I-sections under minor-axis combined loading was evaluated. The evaluation results generally indicated that the codified design interaction curves lead to unduly conservative cross-section resistance predictions, mainly owing to the conservative end points, which are calculated without considering material strain hardening. Finally, improved design interaction curves were proposed through adopting (i) more accurate end points, which are calculated with rational exploitation of material strain hardening by continuous strength method and (ii) more proper shapes, which allow for better representation of the interaction. The proposed design interaction curves were shown to result in substantially more accurate and consistent resistance predictions for stainless steel welded I-sections under compression and minor-axis bending moment than their codified counterparts. The reliability of the new design interaction curves was confirmed by means of statistical analyses.